Career Management Trends in Terms of Gender - Paichadze, Nugzar; Kharadze, Natalia; Giorgobani, Maia; Nikvashvili, Maia (European Journal of Economics and Business Studies, 2019)
Career management is a deliberate process including the involvement of an individual in various activities, resulting in a high level of performance, professional growth. Many people think that the career and the job that we choose represent the goal of our existence, and by this we can demonstrate ourselves and our natural inclinations. Our paper deals with career management. Our interest has been caused by gender peculiarities in career management. Gender Equality gives the opportunity to women and men to have an equal access in all areas of public life. In the course of research we set the hypotheses; Hypothesis HP1: Gender Q2 affects Q1 employment field (1)public sector 2) private sector 3) educational institution;); Hypothesis HP3: Gender Q2 affects Q5 how the respondents were accepted to work (by means of an interview, a contest, a direct manner) where we used the Correlation Analysis, a Chi-square Test; Hypothesis HP2: Gender Q2 affects Q4 work experience. Where we used the Correlation Analysis, the test about Homogeneity of Variance (Levene); Hypothesis HP4: Gender Q2 influences Q15 Are you invited to any kind of meetings? Where a single-factor dispersion analysis is used-One Way ANOVA, Correlation Analysis. The survey showed an interesting picture in terms of gender. The impact of the Georgians cultural values and traditions has been sharply revealed in women’s career management process. Considering the conclusions and recommendations received as a result of the survey will eliminate the problems in women’s career management.